MEASURING HEALTH SERVICES IN PUSKESMAS RUNGKUT SURABAYA - MS, MM, Dr. H. Zakariya,; Gunawan, MM, Drs. Ec. Kunto Inggit; MM., Drs. Ec. Mataji, (JHP17 (Jurnal Hasil Penelitian), 2020)
Until now the people who use the services provided by government agencies still consider that most of the services provided by the government seem to have not been fully satisfactory, even some services seem expensive and very slow. Public services carried out by the government through bureaucrats often receive sharp attention from various groups. Bureaucratic mentality which often abuses power and authority, rampant nepotism in various public service units adds to the blurred picture of services performed by bureaucratic apparatus. As stated by Norman Flyn (1990) public services that are managed by the government herarchically tend to be characterized by over-bureaucratic, bloated, wasteful, and under-performing. These problems are compounded by administrative technical problems that are often said to be inefficient and the stealth costs that are often incurred by the public to obtain services, adding to the increasingly complex quality of service issues run by the bureaucracy. Likewise, health services in Rungkut sub-district are still plagued by administrative technical issues. For this reason, the purpose of this study is to measure the extent of health services in the Rungkut District Health Center. The method used is descriptive quantitative by taking 271 respondents who are doing outpatient treatment from October to December 2019. The results of the study indicate the degree of satisfaction with health services at the Surabaya Rungkut Health Center is generally still at a satisfactory level. With the degree of health services according to respondents still at a satisfactory level, the management of the puskesmas must continue to strive for service personnel to improve their performance so that overall services go up to satisfactory levels and can even be pushed at very satisfying levels. Keywords: Measuring-performance-health services